S04-2: Back to a Healthy Society (BASE): The Co-Creation Process and Structure of the Peer-To-Peer Change Agent Approach of BASE (Baltic Journal of Sport and Health Sciences, 2026)
During COVID-19, older adults faced a higher risk of severe illness and were advised to strictly isolate, which led to increased physical inactivity and social isolation. The pandemic intensified experiences of social exclusion, contributing to both physical and psycho-social challenges. This significantly affected the quality of life of older people across Europe. Against this background, the Back to a Healthy Society initiative saw a need for developing innovative mitigation approaches to (re)connect older people to society so that they could enjoy a healthier lifestyle.To reach this goal, we exploited a two-step activation process: We developed an innovative peer-to-peer change agent approach that engages already active older people in the development of their local communities. They were trained as Active Neighbourhood Buddies to inspire, engage, and empower their peers who are not yet active and have difficulties to (re)connect. We trained our older change agents about a holistic concept of healthy lifestyle, and we helped them to understand basic methods to trigger behavioural change and to activate their peers. In addition, we provided them with support from experienced mentors who form part of the local community ecosystem as professionals. The mentors were trained to exploit a local community of practice approach to support developing an active neighbourhood setting. They assisted the Neighbourhood Buddies in co-creating applicable healthy lifestyle initiatives and to anchor them with local community stakeholders across sectors.For it, our capacity building approach aimed at an active and open learning environment, and it exploited a flexible but interconnected mentoring and learning systematic. It means that our mentoring was adaptable in its implementation approach and tailored towards specific context in practice and individual learning needs. This alternative design for personal capacity building provided the advantage to design change agent programmes that are highly learner-centred and reflective. It ensured to yield at relevant, innovative, and implementable solutions rooted in practice and adapted to the local context of the older persons.As a result, our older change agents became true anchor points in the local communities. They were enabled to find creative ways to help their peers to enjoy a healthier lifestyle.Acknowledgement: The Erasmus+ BASE project was co-funded by the European Union.Keywords: Older adults, healthy lifestyle, healthy living, peer-to-peer, community-based social change